The Role of Financial Sustainability In Mediating The Effect of Green Investment, Profitability, and Firm Size On Idx 30 Companies - Sari, Ika Puspita; Nurwulandari , Andini (Cita Konsultindo Research Center, 2024)
With the fluctuating company value of issuers indexed on IDX 30 for the period 2016-2023, the purpose of this study is to determine and analyze the effect of green investment, profitability, and firm size on firm value, both directly and through financial sustainability. The research approach is quantitative. The population is issuers indexed on IDX 30 which during the research period (2016-2023) remained stable on IDX 30. The sampling technique used purposive sampling technique. The data collection technique for secondary data in this study is the document study technique. The results of the research show that green investment, profitability, and firm size partially have a positive and significant effect on company value, both directly and through financial sustainability